(untitled) - Tomalin, Barry (Thành phố Hồ Chí Minh, 2014)
Be the best you can be in presentations, meetings, negotiations and networking. Collins Key Business Skills gives you the tools you need to succeed in business if English is not your first language.
Keywords: English language,Tiếng Anh,Business communication,Giao tiếp kinh doanh,English language,Tiếng Anh; Business English,Tiếng Anh thương mại,Business English,Problems, exercises, etc.,Tiếng Anh thương mại,Câu hỏi, bài tập,vv